2012
DOI: 10.1246/cl.2012.130
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal-free Coupling Reactions of Aryl Halides

Abstract: Transition metal catalysis plays a leading role in C(sp 2 )C(sp 2 ) bond formation through substitution reactions. On the other hand, a similar type of substitution reaction has recently been achieved without the aid of transition-metal catalysts. In this review, recent transition-metal-free coupling reactions of aryl halides with arenes, alkenes, or aryl Grignard reagents are summarized in view of S RN 1 reaction. Ç IntroductionAryl halides (ArX), readily available aryl electrophiles, do not undergo S N 2 nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…It has also been demonstrated that phenanthroline is a very effective initiator for free radical chain reaction. So a proposed mechanism is illustrated in Scheme on the basis of our experimental results and literature reports . First, the reaction of 1,10‐Phen and t BuOK generates an electron donor L‐dianion.…”
Section: Resultsmentioning
confidence: 79%
“…It has also been demonstrated that phenanthroline is a very effective initiator for free radical chain reaction. So a proposed mechanism is illustrated in Scheme on the basis of our experimental results and literature reports . First, the reaction of 1,10‐Phen and t BuOK generates an electron donor L‐dianion.…”
Section: Resultsmentioning
confidence: 79%
“…In this proposed mechanism, potassium methoxide first coordinates the boron atom of the silylborane 1 to give the silylborane/alkoxy base complex A, whose existence was suggested by the 11 B NMR experiment [25]. On the basis of the studies on the reactions of silyllithium species and organohalides reported by Strohmann and co-workers [55,56], the aryl anion species seems to be produced subsequently through the formation of the ate complex B, which is generated via nucleophilic attack of the silyl group to the Br atom of the aryl bromide [57][58][59][60][61]. Next, the aryl anion attacks the boron electrophile preferentially rather than silyl bromide to give the corresponding aryl pinacol borate, followed by the reaction of methoxide with the in situ generated silyl bromide.…”
Section: Pmentioning
confidence: 99%
“…Interestingly, Shirakawa and Hayashi’s team initially embarked on the iron‐catalyzed direct coupling reaction of arene and aryl halides. They unexpectedly found that an iron catalyst was not necessary in this coupling reaction 16b. During the process to optimize the reaction conditions, 4,7‐diphenyl‐1,10‐phenanthroline (Bathophen) and NaO t Bu was found to be the most efficient combination for catalyzing direct arylation of benzene with 4‐iodotoluene (Scheme ).…”
Section: Intermolecular C(aryl)c(aryl) Bond Formationmentioning
confidence: 99%